Pengaruh Kepuasan Kerja dan Kompensasi Terhadap Turnover Rate Karyawan Hotel Feodora Airport Palembang - Putri Arista; Endah Dewi Purnamasari; Mohammad Kurniawan Darma Putra (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This study aims to determine the effect of job satisfaction and compensation on the employee turnover rate of Hotel Feodora Airport Palembang. This research carried out on all employees using a saturated sample technique of 132 people. The primary data of this study were obtained through questionnaires and processed using a quantitative approach with the SPSS statistical test tool version 25.00 For Windows. based on results the research conducted found that the variable job satisfaction (Xâ‚) and Compensation (Xâ‚‚) has a negative and significant effect on the turnover rate Employees of Hotel Feodora Airport Palembang (Y). Linear regression test results is obtained the value of the coefficient of job satisfaction (Xâ‚) of -0.786 and the value compensation regression coefficient (Xâ‚‚) of -0.183 with a significance level of 0.000 < 0.05. T test results variable of job satisfaction (Xâ‚) of -13.853 and compensation (Xâ‚‚) of -4.113 with a significance level of 0.000 < 0.05 partially job satisfaction and compensation have a negative and significant effect on the turnover rate. The results of the F test obtained F count of 204.419 with the level significance of 0.000 < 0.05 which means that simultaneously job satisfaction (Xâ‚) and compensation (Xâ‚‚) have a negative and significant effect on the turnover rate.